PERAN PEMERINTAH DALAM MENGUPAYAKAN HAK ATAS UPAH YANG LAYAK BAGI PEKERJA (STUDI PADA DINAS TENAGA KERJA DAN PERINDUSTRIAN KOTA SURAKARTA) - Wulandari, Wulandari; Rejekiningsih, Triana; Nuryadi, Muhammad Hendri (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2019)
This research has aims to know: 1) employee’s, entrepreneur’s, and government’s perception about proper payment, 2) Government’s role, labor offices and industrial, strives for proper payment, 3) problem and government’s problem solve to strive proper payment.This research used qualitative research method with purposive sampling technique. Data collecting technique which is used are observation, interview and documentation. Trustworthiness of the Data which is used is source of the data triangulation and triangulation method. The data analysis of the research used interactive analysis method.The results of the research show that: 1) there are some of differences perception between employee, entrepreneur, and government on proper payment. Employees have a hunch that proper payment is payment which appropriate with their requirement. According to entrepreneur’s point of view, proper payment is payment which is agreed by both of employees and entrepreneur. Whereas, according to government’s proper payment is payment which appropriate with requirement based on KHL calculation. 2) Surakarta Labor Offices and industrial’s role about minimum payment are; a) payment minimum calculation, b) suggesting to Regent or Mayor, c) doing monitoring, d) giving punishment. Whereas in the principal structure and payment scale; a) giving training and socialization, b) doing monitoring, c) giving punishment. 3) problems ; a) entrepreneur’s less understanding  about structure and payment scale, b)there is entrepreneur which is burdened and do not arrange the structure and payment scale. Problem solutions; a) giving socialization and training to entrepreneur, b) giving administration punishment to the entrepreneur which do not arrange the structure and payment scale.  Keywords: authority, payment, employees, labor offices and industrial.